Covid-19 in the light of Erving Goffman. Distancing or relational closure - Pascal LARDELLIER (ACROSS)
In the midst of the Covid-19 crisis, the ordeal of confinement and the distancing from others reminds us by default of the fundamental role played by rites and civility in our relationships. This proves the tremendous topicality of the work of Erving Goffman, the most famous representative of microsociology. Relationships know territories, borders and fences, invisible but pressing, which we do not cross thoughtlessly. However, Covid has reaffirmed these borders, while tightening the fences, the fault of distancing and barrier gestures, but also of general mistrust of others, which may be contaminating.